A compact GBMO applied to modify DV-Hop based on layers in a wireless sensor network. (14th February 2022) - Pan, Jeng-Shyang; Gao, Min; Li, Jian-Po; Chu, Shu-Chuan
Gases Brownian motion optimisation (GBMO) has been shown as a useful optimisation method. The compact concept is implemented to the GMBO named compact gases Brownian motion optimisation (CGMBO) so as to improve the efficiency and effectiveness of the GMBO. Simulation results based on the 23 test functions consisting of the unimodal, multimodal, fixed-dimensional functions and composite multimodal functions demonstrate the superiority of the proposed CGMBO. The idea of layer concept is also proposed to implement the distance vector-hop (DV-Hop) by modifying the original average distance of each hop called layer DV-Hop (LDV-Hop), experimental results also show the proposed LDV-Hop really improve the average positioning accuracy of each node for wireless sensor network. Finally, the proposed CGMBO is combined with the proposed LDV-Hop so as to greatly reduce the position error compared with the DV-Hop. The actual error per-hop distance between nodes is large. When the calculated average hop distance of the nodes does not reach the ideal value, the actual distance between the nodes and the calculated distance will have a large deviation.